Analysis of covers in magazines of general information publications during the Second Republic - Sánchez Vigil, Juan Miguel; Olivera Zaldua, María; Nebreda Mar´tin, Lara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Illustrated magazines played a major role in the communicative process during the first third of the 20th century. The front covers of the publications took on greater importance for attracting the attention of the general public. This study presents an analysis of the cultural contents of the covers of the illustrated general information magazines published during the Second Spanish Republic, with two main goals: to determine if a significant change was produced in the communicative model and to discover the nature of the contents. Five magazines have been analyzed: Blanco y Negro, Nuevo Mundo, Mundo Gráfico, Estampa and Crónica.